Overcoming Algebraic Misconceptions that Inhibit Students' Progress in Mathematical Sciences Final Report. - Bardini, Caroline; Pierce, Robyn (Office for Learning and Teaching, 2014)
Decreasing student participation and progression in mathematical sciences is a major concern. Sound algebraic conceptions are important for success in mathematics. A recent change in secondary school mathematics involves the increasing use of software, including computer algebra systems, which automate some tasks and provide multiple representations of mathematics. It is currently hypothesised that implicit computations/transformations and the syntax of computing technologies may alter students' use and understanding of algebra, creating different challenges for tertiary educators. This is the final report from a pilot project that collected data from first year mathematics and statistics students using an online test followed by 20 in-depth student interviews to ascertain (i) students' background experience with mathematics-learning technology and (ii) their fundamental algebraic conceptions. This will provide an evidence base for creating and piloting quick online assessments that reveal thinking about algebra and provide immediate online feedback as to appropriate remedial teaching strategies including how students might make effective use of technology to support their own learning.